β-Correction Spectrophotometry to Improve the Determination of Trace Amounts of Cobalt with 1-(2-Pyridylazo)-2-Naphthol - Gao, Hong-Wen; Zou, Feng; Zhang, Peng-Fei (Asian Journal of Chemistry, 2010)
Cobalt has been determined in ammoniacal solution with 1-(2-pyridylazo )-2-naphthol (PAN) by β-correction. spectrophotometry. The reaction is sensitive and very selective in the presence of thiourea to mask other ions. β-correction spectrophotometry is a new analytical method and it can eliminate completely the effect of excess PAN in its Co(II) coloured solution to give out the real absorbance of the produced Co-PAN complex. All of the sensitivity, precision and accuracy are increased. With the help of the updated principle the complex-ratio of the formed chelate and its true molar absorptivity and its instability constant have been still determined. Results for cobalt showed that the detection limit was 0.014 mg/L and Beer's law was obeyed over the concentration range 0–1.20 mg/L Co at 620 nm. It has been applied to the determination of trace amounts of cobalt in environmental water with satisfactory results.